Reproducing Mane’e: Social Practices and Cultural Continuity in the Kakorotan Island Community - Junianti Sahea; Ferdinand Kerebungu; Sangputri Sidik (DISCOURSE: Indonesian Journal of Social Studies and Education, 2026)
The Mane’e tradition in one of the island communities of the Talaud Islands is not merely a cultural performance, but a way in which people organize their shared life with the sea. Through this practice, fishing is not treated as an individual activity, but as something that is arranged, limited, and decided together. In recent years, however, this tradition has been placed under pressure. Changes in fishing technology, economic needs, shifting ways of life, and the reduced involvement of younger people have all affected how Mane’e is carried out. This study looks at how Mane’e continues to exist in such conditions. It focuses on the ways the community keeps the practice alive through everyday social relations, rules that are agreed upon together, and the passing of knowledge from one generation to the next. The research is based on field interviews, observations, and documentation of community practices. The findings show that Mane’e is maintained because people continue to take part in it, not only during the ritual itself but also in the decisions and preparations that surround it. Community discussions, the sharing of responsibilities, and the learning process between older and younger generations all play a role in keeping the practice going. The eha rule, which sets a period when the sea cannot be used, is especially important. It is not just a restriction, but a shared agreement that shapes how people relate to marine resources and to each other. At the same time, Mane’e is not unchanged. Its form and meaning shift as the community responds to new economic demands and the growing presence of tourism. What remains constant is not the form of the ritual, but the way people continue to negotiate its place in their lives. This study concludes that the survival of Mane’e depends on how people keep working it into their social life—through cooperation, shared rules, and the passing of knowledge—while also adjusting it to the changes around them.